2015
DOI: 10.1128/jvi.01076-15
|View full text |Cite
|
Sign up to set email alerts
|

2′-5′-Oligoadenylate Synthetase-Like Protein Inhibits Respiratory Syncytial Virus Replication and Is Targeted by the Viral Nonstructural Protein 1

Abstract: 2=-5=-Oligoadenylate synthetase-like protein (OASL) is an interferon-inducible antiviral protein.Here we describe differential inhibitory activities of human OASL and the two mouse OASL homologs against respiratory syncytial virus (RSV) replication. Interestingly, nonstructural protein 1 (NS1) of RSV promoted proteasome-dependent degradation of specific OASL isoforms. We conclude that OASL acts as a cellular antiviral protein and that RSV NS1 suppresses this function to evade cellular innate immunity and allow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
31
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 40 publications
3
31
0
Order By: Relevance
“…We also show for the first time that the NS proteins of PVM promote degradation of selected murine ISGs, the most distal arm of the type I IFN pathway. Recent studies, including ours, have shown that at least two ISGs can act as antivirals against RSV; they are viperin and OASL323336. We also showed that RSV NS1 could degrade OASL, allowing better RSV growth33.…”
Section: Discussionsupporting
confidence: 69%
See 3 more Smart Citations
“…We also show for the first time that the NS proteins of PVM promote degradation of selected murine ISGs, the most distal arm of the type I IFN pathway. Recent studies, including ours, have shown that at least two ISGs can act as antivirals against RSV; they are viperin and OASL323336. We also showed that RSV NS1 could degrade OASL, allowing better RSV growth33.…”
Section: Discussionsupporting
confidence: 69%
“…Recent studies, including ours, have shown that at least two ISGs can act as antivirals against RSV; they are viperin and OASL323336. We also showed that RSV NS1 could degrade OASL, allowing better RSV growth33. It is reasonable to assume that the NS proteins of both viruses are capable of inhibiting or degrading many more members of the ISG family that need to be identified.…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…Further studies are required to determine its effect on other RNA or DNA viruses. It has previously been reported that viruses may evade innate immunity by inhibiting OAS expression through self-encoded structural or non-structural proteins [41][42][43][44][45]. Whether such mechanism exists in PRRSV, and which protein is specific to this virus, remain to be determined.…”
Section: Discussionmentioning
confidence: 99%